SIMULATION OF VINPOCETINE RELEASE PROCESS FROM MICROCAPSULES WITH HYDROPHOBIC SHELL - Yu. A. Polkovnikova; A. A. Glushko; I. Yu. Mikhailovskaya; Yo. S. Karieva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
Nowadays microcapsules are widely spread in different industries. Microcapsules with vitamins, etheric and fatty oils are included into different cosmetics (creams, gels, serums). Microencapsulated probiotics are used in foods and fodder additives in veterinary. An important field of application of microencapsulation in pharmacy is the combination in the total dosage of drugs that are incompatible when mixed in free form.The aim of work is a comparative analysis of thermodynamic characteristics of vinpocetine release from the melt of beeswax and cacao butter 3:2 into water, solution of hydrochloric acid 0.01 M and ethanol.Materials and methods. For simulation of the process of vinpocetine release from the melt into different environments models component models of the studied systems were built and their atom charges were calculated by quantum-chemical method. Spatial models of the components were built in Hyper Chem 8.01. As an initial state for the thermodynamic characteristics of the calculation of vinpocetine release from the melt, a conformation of «melt-vinpocetine» system was used after thermodynamic equilibration by molecular dynamics simulation in Bioeurica program for 5 ns. For isolated systems a vibrational analysis was performed with the use of unrestricted Hartree-Fock method in STO-3G basis set in Orca 4.0 program.Results and discussion. Vinpocetine release from the melt of beeswax and cacao butter 3:2 into water with different pH values and to ethanol depends on its solubility in these environments, and also on solubility of the melt.Conclusion. The performed study of vinpocetine release from the melt of beeswax and cacao butter 3:2 by molecular dynamics simulation demonstrates the opportunity of vinpocetine release into water with pH=2 and into ethanol. The obtained results make it possible to assume a lower degree of vinpocetine release from the melt into ethanol compared with the solution of hydrochloric acid 0,01 M.